Comparison between Standing and Supine Lateral Radiographs in Low Grade Spondylolisthesis - Dhakal, Gaurav Raj; Biswas, A; Rathinavelu, S; Patel, D Kumar K; Basu, S (Journal of Manmohan Memorial Institute of Health Sciences, 2015)
To analyze the differences between standing and supine plain film lateral radiographs of the lumbosacral region in low grade (grade I/II) spondylolisthesis using the Picture Archiving and Communication System (PACS) software. Demonstrable difference might be a parameter of instability which might be useful in planning surgical treatment when it is too painful for patients to undergo flexion/extension Xrays.Radiographs of 23 patients with low grade spondylolisthesis were analyzed for percentage slip, lumbar lordosis, disc height, sacral inclination and slip angle. These standing and supine lateral radiographs were taken at the same distance with the same magnification. Measurements obtained were statistically analyzed with the SPSS software using the student t test for statistical significance (p<0.05).A significant difference (p < 0.05) was found between the standing percentage slip (mean 36.85% ± 12.78%) and supine percentage slip (mean 27.39% ± 11.14%) (p = 0.01). Similarly, standing lumbar lordosis (mean 37.74% ± 10.96%) and supine lumbar lordosis (mean 30.96% ± 12.76%) revealed a marginally higher p value (p =0.06). However, differences in the disc space height (p=0.09), sacral inclination (p=1) and slip angle (p=0.55) did not show any statistical significance. The standing radiographs effectively demonstrate the increase in slip percentage. This can have a significant impact on the grading of slip which can influence the treatment strategy. Also the increase of slip values on standing Xrays adds a parameter of instability which might be considered in the management strategy. DOI: http://dx.doi.org/10.3126/jmmihs.v1i4.11996 Journal of Manmohan Memorial Institute of Health Sciences Vol. 1, Issue 4, 2015 Page: 14-18